"Kar se zasliši od vzhoda in severa znani grozoviti krik: 'Alah, Alah!'" - Kalčić, Špela (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2007)
The article deals with the Slovene variant of border Orientalism through the perspective of the Slovene intellectual production, combining historic facts with fiction, regarding the period of the Turkish assaults . These aremyths on Moslems as Turks , which were created in those parts of Europe, which in the past were for a considerable period of time subject to Ottoman predatory invasions (compare Gingrich 1998). Slovene historiography, fiction and textbooks are a rich source of such myths, representing, apart from media images on the crises at Middle East, as well as terrorist attacks worldwide, the main source of knowledge on Islam and Moslems in Slovenia. This knowledge is rather questionnable, as historic myths sources on Turkish period are coloured by modern nationalistic view, where Others, mainly Turks as Moslems are used to build Slovene national identity and establish Slovene territory. This is a useful political instrument in the Slovene collective psyche, often misused by various nationalistic and islamophobic actors.
Keywords: islam; Slovenia; Slovenija; kulturna zgodovina; nacionalizem; nationalism; islamofobija; nacionalna identiteta